2022
DOI: 10.1093/braincomms/fcac229
|View full text |Cite
|
Sign up to set email alerts
|

In vivo neuroimaging evidence of hypothalamic alteration in Prader–Willi syndrome

Abstract: Prader-Willi syndrome is a genetic neurodevelopmental disorder with an early phenotype characterised by neonatal hypotonia, failure to thrive, and immature genitalia. The onset of hyperphagia in childhood and developmental, physical and neuropsychiatric characteristics indicate atypical brain development and specifically hypothalamic dysfunction. Whether the latter is a consequence of disruption of hypothalamic pathways for genetic reasons or due to a failure of hypothalamic development remains uncertain. 20 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…However, limited by segmentation methods, most of the studies have not found significantly hypothalamic structural abnormality (Honea et al, 2012;Lukoshe et al, 2017). Recently, using the same Hypothalamic Subunits tool as in this manuscript, Brown et al (2022) reported PWS adults had smaller volumes of whole hypothalamus and its subunits except for right a-iHyp, than that in obese and control adults. Consistent with the results of PWS adults, atrophy of the bilateral hypothalamus in PWS children was found in our study, specifically contributed by the bilateral in fTub andposHyp, right supTub and left a-iHyp subregions.…”
Section: Discussionmentioning
confidence: 71%
“…However, limited by segmentation methods, most of the studies have not found significantly hypothalamic structural abnormality (Honea et al, 2012;Lukoshe et al, 2017). Recently, using the same Hypothalamic Subunits tool as in this manuscript, Brown et al (2022) reported PWS adults had smaller volumes of whole hypothalamus and its subunits except for right a-iHyp, than that in obese and control adults. Consistent with the results of PWS adults, atrophy of the bilateral hypothalamus in PWS children was found in our study, specifically contributed by the bilateral in fTub andposHyp, right supTub and left a-iHyp subregions.…”
Section: Discussionmentioning
confidence: 71%
“…In this model PWS might be considered to be a single gene disorder in which the phenotype arises as a consequence of abnormal brain development driven by the absence of expression of SNORD 116. A paper by [ 2 ] reported on recent neuroimaging findings showing significantly smaller hypothalamic nuclei in people with PWS compared to an aged-matched typically developing control group and also an obese group. The authors argue that the hypothalamus fails to develop in PWS and this would explain the varied phenotypic characteristics of hypothalamic origin.…”
Section: Genotype To Phenotypementioning
confidence: 99%
“…We identify what we consider to be particular key questions that need to be addressed and suggest hypotheses as to how the absence of expression of this gene gives rise to the phenotype. We propose that this is either due to a direct effect on brain development, particularly affecting the hypothalamus [ 2 ] by impacting on foetal nutrition or by failing to modify the expression levels of a cascade of other (as yet unidentified) genes, which in turn affect brain development. The ultimate effect of the pattern of atypical brain development specific to PWS is to alter the response thresholds for particular networks in the brain thereby impairing the ability to maintain homeostasis, such as ensuring energy balance or responding to environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort of 12 children with Prader–Willi syndrome, 18 obese children without Prader–Willi syndrome, and 18 healthy controls, Wu et al showed that children with Prader–Willi syndrome have a significantly smaller thalamus, globus pallidus, hippocampus, amygdala, nucleus accumbens, deep cerebellar nuclei, and hypothalamus [ 4 ]. Brown et al found similar differences with regard to the atrophy of hypothalamic nuclei, but they also showed that a lower whole hypothalamus volume was significantly associated with higher body mass index in Prader–Willi syndrome [ 5 ]. They described that an increased preoccupation with food was associated with lower volumes of the bilateral posterior nuclei and left tubular superior nucleus of the hypothalamus [ 5 ].…”
Section: Introductionmentioning
confidence: 96%
“…Brown et al found similar differences with regard to the atrophy of hypothalamic nuclei, but they also showed that a lower whole hypothalamus volume was significantly associated with higher body mass index in Prader–Willi syndrome [ 5 ]. They described that an increased preoccupation with food was associated with lower volumes of the bilateral posterior nuclei and left tubular superior nucleus of the hypothalamus [ 5 ].…”
Section: Introductionmentioning
confidence: 96%